2018
DOI: 10.1016/j.rser.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor thermal comfort by different heat mitigation strategies- A review

Abstract: Due to the ongoing global warming, heat mitigation strategies are becoming implemented through practice and simulations. These efforts aim to make the cities that are dealing with the urban heat island more livable. The effect of heat mitigation strategies on climate condition and energy consumption have been studied and compared, previously. In this paper, the effect of these strategies on human thermal comfort in urban open spaces is reviewed. Specifically, the review is focused on vegetation (in the form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
160
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(166 citation statements)
references
References 70 publications
1
160
0
5
Order By: Relevance
“…As a result, several studies have suggested using 'cool' reflective surfaces with higher albedo to decrease the surface temperature. These surfaces include both cool roofs [49][50][51][52][53][54] and cool pavements [55][56][57][58][59]. Synnefa et al [60] conducted a numerical evaluation of the benefits of the large-scale deployment of reflective surfaces in Athens, Greece and found a potential reduction of ambient air temperatures by up to 2 • C. Another study by Georgiakis et al [61], also in Athens, suggested a more moderate decrease in ambient air temperature, of about 1 • C, although only for a single urban canyon.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several studies have suggested using 'cool' reflective surfaces with higher albedo to decrease the surface temperature. These surfaces include both cool roofs [49][50][51][52][53][54] and cool pavements [55][56][57][58][59]. Synnefa et al [60] conducted a numerical evaluation of the benefits of the large-scale deployment of reflective surfaces in Athens, Greece and found a potential reduction of ambient air temperatures by up to 2 • C. Another study by Georgiakis et al [61], also in Athens, suggested a more moderate decrease in ambient air temperature, of about 1 • C, although only for a single urban canyon.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is focused on pedestrians' thermal comfort in outdoor environment where there is limited access to a cool spot or a cold drink. Thermal comfort is defined as "that condition of mind which expresses satisfaction with the thermal environment" (ISO-7730 2005).Thermal comfort includes environmental factors (such as air temperature and wind speed), biological factors (such as age and gender), and physiological factors (such as clothing and metabolism) (Ali-Toudert and Mayer 2007;Nicol et al 2012;Taleghani 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This trend shows that these serious urban climate hazards have not been adequately tackled, especially considering that it has a relevant impact at the energy, environmental and social levels, as widely documented in several exemplary studies [10][11][12][13][14][15]. On the contrary, several mitigation strategies and technologies are available to counter this phenomenon.…”
Section: Introductionmentioning
confidence: 99%